Aortic Elastic Properties in Preschool Children Born Preterm. Issue 11 (November 2016) - Odri Komazec, Irena; Posod, Anna; Schwienbacher, Martin; Resch, Maria; Pupp Peglow, Ulrike; Kiechl, Stefan; Baumgartner, Daniela; Kiechl-Kohlendorfer, Ursula
Abstract : Objective—: Preterm birth predisposes children to the development of cardiovascular diseases in adulthood. The aim of this study was to characterize elastic properties of the aorta at preschool age and test the hypothesis that prematurity is associated with decreased aortic distensibility and increased stiffness, both of which are predictors of increased cardiovascular risk. Approach and Results—: In an observational study of 76 five- to seven-year-old children born at a gestational age <32 weeks and 79 term-born controls, elastic parameters of the ascending and descending abdominal aorta were determined noninvasively by means of M mode echocardiographic tracings and calculated using computerized wall contour analysis. Compared with children born at term, the preterm group showed significantly reduced distensibility and increased stiffness of the descending abdominal aorta. These results remained significant under multivariable adjustment for birth weight z score, maternal smoking in pregnancy, maternal education, family history of cardiovascular disease, breastfeeding, childhood nutrition, and current body mass index z score (multivariable odds ratios and 95% confidence intervals 5.1, 1.7–15.9; P =0.005 and 2.8, 1.0–7.9; P =0.046, respectively). Further adjustment for intravenous lipid therapy attenuated the strength of association. Elastic properties of the ascending aorta did not differ between the 2 study groups. Conclusions—: Children born preterm are characterized by decreased elastic properties of the descending abdominal aorta potentially attributable to impaired viscoelastic properties of and lipid damage to the aorta. Clinical follow-up of preterm infants with a focus on aortic elastic properties may be useful for tailoring early prevention programs and counteracting cardiovascular risk in adulthood. Abstract : Supplemental Digital Content is available in the text.